Determinación de los Contaminantes producto de la Combustión por fuentes móviles a Gasolina en el Cantón Pujilí Empresa Pública de Movilidad de la Mancomunidad de Cotopaxi, Provincia de Cotopaxi período 2017. - Otáñez Sánchez, Esteban Vicente (2018)
The purpose of this research is to provide technical data that reflects the current situation regarding atmospheric pollution generated by mobile sources of combustion of gasoline in Pujilí Canton, which allows taking corrective actions in favor of the health of its inhabitants. The monitoring was conducted in the facilities of the Public Mobility Company of the Commonwealth of Cotopaxi and allowed to verify compliance with the Ecuadorian technical standard for the control of air quality. The study was conducted on a sample of 381 vehicles by static test applying the methodology established in the NTE INEN 2 203, using the equipment for gas analysis AVL DiTest Gas 1000. The results obtained have been compared with the Table N° 1 of the Maximum limits of emissions for mobile petrol sources in minimum gear or idle of the Ecuadorian Technical Standard NTE INEN 2 204. For the carbon monoxide (CO) parameter 86,35% representing 329 vehicles of the sample met the established standard and 13,65% representing 52 cars did not comply; while 200 vehicles equivalent to 52,49% fulfilled the setting for unburned hydrocarbons (HC) and 181 equivalent vehicles equivalent to 47,51% did not meet the standard when exceeding the permissible limits of HC in their respective categories.